2013
DOI: 10.5194/tcd-7-4913-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transition of flow regime along a marine-terminating outlet glacier in East Antarctica

Abstract: We present results of a~multi-methodological approach to characterize the flow regime of West Ragnhild Glacier, the widest glacier in Dronning Maud Land, Antarctica. A new airborne radar survey points to substantially thicker ice (> 2000 m) than previously thought. According to the new data, West Ragnhild Glacier discharges 13–14 Gt yr−1. Therefore, it is one of the three major outlet glaciers in Dronning Maud Land. Glacier-bed topography is distinct between the upstream and downstream … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…Callens and others (2014) showed that the downstream part of the West Ragnhild Glacier bed is wide, flat and covered by wet sediments, which induces basal sliding, thus a low coefficient C. At that place, the High-resolution scenario indicates a more slippery bed because of slightly higher (+50 m a −1 ) surface velocities between our flow field and that of Rignot and others (2011b). The sticky bed on Derwael Ice Rise and the western promontory concurs with low velocities and the negligible basal sliding in those areas.…”
Section: Inversion For the Stiffening Factor And Basal Frictionmentioning
confidence: 85%
See 2 more Smart Citations
“…Callens and others (2014) showed that the downstream part of the West Ragnhild Glacier bed is wide, flat and covered by wet sediments, which induces basal sliding, thus a low coefficient C. At that place, the High-resolution scenario indicates a more slippery bed because of slightly higher (+50 m a −1 ) surface velocities between our flow field and that of Rignot and others (2011b). The sticky bed on Derwael Ice Rise and the western promontory concurs with low velocities and the negligible basal sliding in those areas.…”
Section: Inversion For the Stiffening Factor And Basal Frictionmentioning
confidence: 85%
“…Compared with ice shelves of other major outlet glaciers (e.g. Jutulstraulmen and Shirase Glacier), the RBIS flows more slowly (maximum speed ≈345 m a ) and ice is discharged through a comparatively wide gate at the grounding line (Callens and others, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ApRES (Brennan et al, ; Nicholls et al, ) was deployed from January to December in 2016 on the RBIS (Figure ) about 90 km from the ice shelf front and 5 km seaward from the grounded ice on the fast‐flowing portion of the West Ragnhild glacier, which is the third largest outlet glacier along the Dronning Maud Land Coast (Callens et al, ). The ice thickness at the site was ∼300 m in the trough of a channel (Drews, ) but increases up to 600 m in the grounding zone upstream, and ice flow velocities in this region range between 250 and 300 m/a (Rignot et al, ).…”
Section: Data Collection and Processingmentioning
confidence: 99%
“…Here, we present new and highly resolving time series of melt rates observed on the Roi Baudouin Ice Shelf (RBIS), which is part of the belt of slowly melting (Rignot et al, ) smaller ice shelves situated over the narrow continental shelf along the coast of Dronning Maud Land, East Antarctica (Figure ). The observations are taken near the grounding line where the bed lowers toward the interior of the ice sheet (Callens et al, ; Fretwell et al, ) and our analysis explores the oceanographic mechanisms that control basal melting in this region that is potentially susceptible to marine ice sheet instability (Favier et al, ).…”
Section: Introductionmentioning
confidence: 99%